Bis(2-methyl-1H-indole-3-carbaldehyde benzoylhydrazonato-kappa N-2,O)copperII) pyridine disolvate - Ali, Hapipah Mohd; Ng, S.W.; Xie, M.J.; Najwa, M.I. (International Union of Crystallography, 2006)
The Cu atom in the title compound, [ Cu( C17H14N3O)(2)] (.-) 2C(5)H(5)N, is chelated by the deprotonated Schiff base in a square-planar geometry; the amine group of the Schiff base forms a hydrogen bond with a pyridine solvent molecule. The Cu atom lies on a center of inversion.